Application of lithium orthosilicate for high-temperature thermochemical energy storage. (1st May 2017) - Takasu, Hiroki; Ryu, Junichi; Kato, Yukitaka
Highlights: Li4 SiO4 /CO2 system is proposed for use in chemical heat pump systems at 650 and 700 °C. Li4 SiO4 /CO2 system showed an enough cyclic reaction durability for 5 cycles. The energy storage density of Li4 SiO4 was estimated to be 750 kJ L −1 and 780 kJ kg −1 . It was demonstrated that Li4 SiO4 could be used as a thermal heat storage material. Abstract: A lithium orthosilicate/carbon dioxide (Li4 SiO4 /CO2 ) reaction system is proposed for use in thermochemical energy storage (TcES) and chemical heat pump (CHP) systems at around 700 °C. Carbonation of Li4 SiO4 exothermically produces lithium carbonate (Li2 CO3 ) and lithium metasilicate (Li2 SiO3 ). Decarbonation of these products is used for heat storage, and carbonation is used for heat output in a TcES system. A Li4 SiO4 sample around 20 μm in diameter was prepared from Li2 CO3 and SiO2 using a solid-state reaction method. To determine the reactivity of the sample, Li4 SiO4 carbonation and decarbonation experiments were conducted under CO2 at several pressures in a closed reactor using thermogravimetric analysis. The Li4 SiO4 sample's carbonation and decarbonation performance was sufficient for use as a TcES material at around 700 °C. In addition, both reaction temperatures of Li4 SiO4 varied with the CO2 pressure. The durability under repeated Li4 SiO4 carbonation and decarbonation was tested using temperature swing and pressure swing methods. Both methods showed that the Li4 SiO4 sample has sufficient durability. These results indicate that the temperature for heat storage and heat output by carbonation and decarbonation, respectively, could be controlled by controlling the CO2 pressure. Li4 SiO4 /CO2 can be used not only for TcES but also in CHPs. The volumetric and gravimetric thermal energy densities of Li4 SiO4 for TcES were found to be 750 kJ L −1 and 780 kJ kg −1, where the porosity of Li4 SiO4 was assumed to be 59%. When the reaction system was used as a CHP, and heat stored at 650 °C was warmed and output at 700 °C, 14% of the heat supplied by carbonation was needed for self-heating of the material from 650 to 700 °C, and the volumetric and gravimetric thermal energy densities for heat output were calculated as 650 kJ L −1 and 670 kJ kg −1, respectively.